2017
DOI: 10.31729/jnma.3202
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Predictors of Gastro-Oesophageal Varices

Abstract: Introduction: The worldwide accepted tool for screening and monitoring gastro-oesophageal varices in patients with liver cirrhosis is upper gastrointestinal endoscopy. Endoscopy needs clinical expertise and has got its own procedure related complications. Repeated endoscopies may be expensive and patients tend to develop poor compliance. This study was undertaken to establish the role of noninvasive parameters in predicting gastro-esophageal varices. Methods: Two hundred patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 7 publications
2
16
1
Order By: Relevance
“…Of 100 patients studied in the study 76 (76%) were male, similar male predominance of 77%, 69.3% and 86.1% was observed in studies carried out by Bhattarai S et al [12] Mandal L et al [13] and Sharma SK et al [14] respectively. Median age of study population was 52 years which reported similar 54 years as in the study carried out by Bhattrai et al [12] whereas the age was higher in the other above studies 40 and 45 years respectively. Oesophageal varices were detected in 53% of the patients, in contrary higher number of varices were detected in other studies carried out by Bhattrai et al [12] and Mandal L et al [13] [12].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Of 100 patients studied in the study 76 (76%) were male, similar male predominance of 77%, 69.3% and 86.1% was observed in studies carried out by Bhattarai S et al [12] Mandal L et al [13] and Sharma SK et al [14] respectively. Median age of study population was 52 years which reported similar 54 years as in the study carried out by Bhattrai et al [12] whereas the age was higher in the other above studies 40 and 45 years respectively. Oesophageal varices were detected in 53% of the patients, in contrary higher number of varices were detected in other studies carried out by Bhattrai et al [12] and Mandal L et al [13] [12].…”
Section: Discussionsupporting
confidence: 81%
“…Median age of study population was 52 years which reported similar 54 years as in the study carried out by Bhattrai et al [12] whereas the age was higher in the other above studies 40 and 45 years respectively. Oesophageal varices were detected in 53% of the patients, in contrary higher number of varices were detected in other studies carried out by Bhattrai et al [12] and Mandal L et al [13] [12]. Another study by Mandal et al [13] also had lower platelet count with varices111000± 2840/cumm whereas platelet count was 215000 ± 5500/cumm without varices, which was higher then above studies.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…These findings are similar to those reported by Jamil et al with sensitivity of 51.25% (95%CI: 39.8–62.6) and specificity of 65.71% (95%CI: 53.4–76.7) with comparable AUC: 0.591, and a lower cutoff point of 12 mm [37]. High predictive values of the PVD for varices was reported in Nepal at a cutoff point of 12.25 mm (sensitivity: 92.72%; specificity: 90%) [38].…”
Section: Discussionmentioning
confidence: 99%